EMPOWERING LECTURERS IN MANAGEMENT ONLINE JOURNAL SYSTEM - Indra Mukhlis Adnan; Nur Komariah; Wandi Wandi; Ahmad Rifa’i; Bayu Fajar Susanto; Dewi Murni; Irjus Indrawan (KARYA ABDI, 2021)
The lack of lecturer mastery in managing the Online Journal System (OJS) is one of the factors that slows the journal accreditation process. Empowerment of lecturers in the management of OJS aims to increase the role of lecturers as journal managers according to journal accreditation standards. This empowerment method is carried out by means of webinars, workshops, training, and OJS assistance both online and offline. Through workshops, lecturers as journal managers open their mindsets about the importance of managing OJS in accordance with journal accreditation standards, through workshop activities, lecturers are able to design journals and complete journal managers in accordance with accreditation standards, then in training activities, lecturers practice the functions of each manager. OJS and in mentoring activities, lecturers receive assistance for DOI activation, indexation and registration for journal accreditation through the arjuna application. Through lecturer empowerment activities in managing OJS, the number of accredited journals can be increased.